APPLICATION OF 3D TECHNOLOGIES IN ORTHODONTICS - Mirzaeva Adiba Khamdamovna; Yuldasheva Madina Azamatovna (Modern American Journals, 2025)
This article explores the use of 3D technologies in orthodontics, highlighting their advantages and clinical outcomes. Unlike traditional orthodontic methods, 3D technologies (digital scanning, 3D printing, computer tomography) provide higher precision, faster workflows, and greater patient comfort. Digital diagnostics allow for accurate analysis of oral conditions and the development of individualized treatment plans. Moreover, 3D printing enables the fabrication of clear aligners, orthodontic appliances, and surgical templates, which makes treatment more efficient and less invasive. The article emphasizes the role and future potential of 3D technologies in modern dentistry.
Keywords: Orthodontics, 3D technologies, digital diagnostics, 3D printing, aligners.